Optimization of Long Line Management in Seaweed Farming: Strategies for Increasing Farmers' Group Income in Pinrang Regency, Indonesia - Ruslan, Muhlis; Menne, Firman; Indrawati, Erni; ., Hamsiah; Pratiwi, Anggun; Rizal, Andi (Journal of Ecohumanism, 2024)
This research aims to explore the role of the long-line method in increasing the income of seaweed farmers in Pinrang Regency, South Sulawesi, Indonesia, while examining the challenges they face and the strategies they employ to overcome them. The study employs a qualitative case study approach, involving 15 seaweed farmers from various coastal villages within Pinrang Regency, representing diverse demographic backgrounds and experiences. Data collection was conducted through semi-structured interviews, allowing for an in-depth understanding of the participants' farming practices and challenges. The findings indicate that seaweed farmers increase their income by optimizing resources, collaborating within farmer groups, and adapting to environmental and market changes. Strategies such as space optimization, material reuse, and knowledge sharing among farming communities significantly enhance productivity and sustainability. Furthermore, farmers employ adaptive techniques to mitigate environmental risks and market volatility, including using durable materials and processing seaweed into higher-value products. The implications of these findings are crucial for policymakers and development organizations, as they highlight the potential of sustainable farming practices in improving the livelihoods of coastal communities. Policymakers are encouraged to develop support programs that promote resource optimization, foster community-driven farming networks, and train farmers in adaptive strategies. However, the study's limitations, including the small sample size and reliance on self-reported data, may affect the generalizability of the results. Future research should incorporate larger, more diverse samples and objective measures to enhance the robustness of the findings, and explore the long-term impacts of the long-line method on income and sustainability.